2000
DOI: 10.1037/1040-3590.12.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted judgment: Defining strengths and liabilities.

Abstract: Clinicians often fail to recognize limitations in their own subjective judgments, make use of well-developed mechanical-prediction methods, or carefully evaluate which computer-based aids warrant their consideration. This article addresses issues regarding computer-based test interpretations (CBTIs) and computer-based decision making. Comments highlight conclusions reached by other contributors to this Special Section, additional literature bearing on these observations, and implications for consumers of compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…But for multi-parametric studies, the amount of data can be overwhelming even for expert readers, and conventional qualitative image interpretation may lead to inconsistent diagnostic precision. In recent years artificial intelligence and machine learning methods have been proven useful for diagnostic decision making problems in high dimensional feature space (23, 24). Support vector machine (SVM) learning is based on structural risk minimization (SRM) rather than the traditional empirical minimization (ERM) principle.…”
Section: Introductionmentioning
confidence: 99%
“…But for multi-parametric studies, the amount of data can be overwhelming even for expert readers, and conventional qualitative image interpretation may lead to inconsistent diagnostic precision. In recent years artificial intelligence and machine learning methods have been proven useful for diagnostic decision making problems in high dimensional feature space (23, 24). Support vector machine (SVM) learning is based on structural risk minimization (SRM) rather than the traditional empirical minimization (ERM) principle.…”
Section: Introductionmentioning
confidence: 99%
“…While they were positive about the results reached with the system, few indicated that they would use it in practice [79]. Criticisms of these systems fall into general categories of requiring too much data entry, limited in the decision areas (designed to only address a single clinical issue), inconvenient to access or viewed as a challenge to professional capability [72,73,79].…”
Section: Inference (Knowledge) Enginementioning
confidence: 98%
“…Instead, test norms and the validity and reliability should be considered for each version of a test, whether it is paper-and-pencil or computer-based. Both Garb (2000) and Snyder (2000) noted that validity studies of computer and Internet-based assessment are rare. Even if a computer-based measure has satisfactory psychometric properties, the test scores should always be interpreted in association with other data, such as supplementary test scores and an individual interview, if possible.…”
Section: Ethical Issues In Computer and Internet-based Career Assessmentmentioning
confidence: 99%